Acoustic rhinometry and video endoscopic scoring to evaluate postoperative outcomes in endonasal spreader graft surgery with septoplasty and turbinoplasty for nasal valve collapse. Issue 1 (December 2016) - Erickson, Bree; Hurowitz, Robert; Jeffery, Caroline; Ansari, Khalid; El Hakim, Hamdy; Wright, Erin; Seikaly, Hadi; Greig, Sam; Côté, David
Abstract Background Nasal obstruction is a common complaint seen by otolaryngologists. The internal nasal valve (INV) is typically the narrowest portion of the nasal cavity, and if this area collapses on inspiration the patient experiences significant symptoms of nasal obstruction. The nasal obstruction is further compounded if the INV is narrower than normal. Previous studies have evaluated the effectiveness of techniques to alleviate structural nasal obstruction, but none have looked specifically at spreader grafts measured by acoustic rhinometry or validated grading assessment of dynamic INV collapse. Our objective was to evaluate the application of acoustic rhinometry coupled with visual endoscopic grading of the INV, and validated subjective measurements, in patients undergoing endonasal spreader graft surgery with septoplasty and turbinoplasty. Methods This is a prospective clinical study conducted within a tertiary care rhinoplasty practice. Patients undergoing septoplasty and bilateral inferior turbinoplasty with bilateral endonasal spreader graft placement for observed internal nasal valve collapse were recruited. Baseline, early and intermediate postoperative measures were obtained. The primary outcome was grading of the INV collapse on video endoscopy. Secondary outcomes included cross-sectional area at the INV measured by acoustic rhinometry, subjective Nasal Obstruction Symptom Evaluation (NOSE) and Sino-Nasal Outcome Tool (SNOT-22) scores. Results A total of 17 patients, average age of 34.5 ± 12.2 years, undergoing septoplasty, bilateral endonasal spreader grafts, and bilateral turbinoplasty were included in the study. Postoperative measurements were performed at an average of 8.1 ± 1.6 weeks and 17.7 ± 4.2 weeks. Patients had significant improvement for INV collapse grading, cross-sectional area, NOSE and SNOT-22 scores in both the early and intermediate follow up. Endoscopic grading had moderate inter-rater agreement (κ = 0.579) and average intra-rater agreement (κ = 0.545). Conclusions This study is the first to demonstrate a statistically significant improvement of objective measurement of internal nasal valve function, both static and dynamic, and subjective improvements. This supports endonasal cartilagenous spreader grafts with septoplasty and inferior turbinoplasty for patients with nasal obstruction with internal nasal valve collapse.